KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL BERDASARKAN TIPE ADVERSITY QUOTIENT - Aisyah Rahmayantri; Nanang Priatna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
The purpose of this research is to describe students’ problem solving ability through mathematics subject. The focus is especially at narrative questions in social arithmetic material on VII grade students. Seeing as the problem solving ability has four indicators such as: 1) the identification of problem, 2) formulating strategy, 3) conducting strategy, and 4) evaluating solution, this description is also considering the type of adiversity quotient (AQ). The research subject involved 28 students on VII grade level of Mts Negeri 8 Majalengka who have studied social arithmetic material. Then, the subjects are classified according to the type of AQ which are Climber, Camper, and Quitter. The data collection technique used is questionnaire, problem solving test, and interview. In analysing the data, the researchers used data reduction, data serving, and drawing conclusion or verification. This research focused on problem solving ability through social arithmetic material that wrapped into narrative questions which closely related to students’ daily activities. The result shows that students with Climber type accomplish all indicators of problem solving ability. However, the Camper type of students reached only three indicators, and students with Quitter type showed only get as far as one indicator draw up.